VICTIMS STATUS IN INDIAN CRIMINAL JUSTICE SYSTEM WITH EVOLUTION - Kaur, Manjinder; Arti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The first stage in the victim’s journey to justice via the criminal justice system is reporting a crime. However, quite often, victims opt not to report the incident. As a result, the perpetrator escapes punishment and they never interact with the criminal justice system. The goal of justice is thereby undermined. In the criminal justice system, victims are crucial. They must thus take an active role in the criminal justice system. The role of victims in the criminal justice system has significantly increased with the advent of restorative justice. However, these rights may encounter resistance in their use as victim involvement in sentencing choices challenges customs and established patterns within criminal courts. On the other hand, when legal cultures shift and the victim is widely recognized as a legitimate participant in criminal proceedings, victim involvement may become a common practice and a means of incorporating elements of restorative justice into adversarial court systems. This study aims to investigate the victim’s function within the criminal justice system and how it helps victims obtain justice. With an emphasis on the Indian criminal justice system, the historical evolution of the position of crime victims in common-law criminal justice systems has been explained. The study article explains the significant participation rights that victims are granted under the Code of Criminal Procedure, 1973 (CrPC). The researcher investigates the apparent discrepancy between the victim’s rights and their actualization. The researcher stresses the need for victim-sensitive behavior from the criminal justice system. New and creative methods for including victims into procedures have been studied. The implications of criminal justice policy on crime victims are covered in the study paper’s conclusion. “For too long, the victims of crime have been the forgotten persons of our criminal justice system. Rarely do we give victims the help they need or the attention they deserve. Yet the protection of our citizens – to guard them from becoming victims – is the primary purpose of our penal laws. Thus, each new victim personally represents an instance in which our system has failed to prevent crime. Lack of concern for victims compounds that failure. ”